ADVISABILITY OF PERFORMING SIMULTANEOUS GYNECOLOGIC SURGICAL PROCEDURES FOR COLON CANCER - Yu. G. Panidi; K. I. Zhordania; V. Yu. Selchuk; Yu. A. Barsukov; V. S. Ananyev; B. P. Kopnin; T. P. Kazubskaya; O. A. Anurova; P. Z. Kutaliya (Опухоли женской репродуктивной системы)
The last decade is characterized by increased concern with problems of primary multiple neoplasm phenomena. Authors discuss vari- ous diagnostic methods used in the management of patients with multiple malignancies, in particular, in patients with colon cancer. Applicability of performing simultaneous gynecologic surgical procedures for colon cancer is evaluated.